Forensic Capacity Building at the Provincial Level: Implications for Police Investigative Practices in Cavite, Philippines - Leocadio S. C. Santiago Jr.; Elizabeth Buena-Villa; Julius Guiller G. Luis (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study examined the contribution of the Provincial Forensic Team (PFT) to the effectiveness and efficiency of investigative operations in local police stations in Cavite. The research aimed to evaluate how forensic support enhances criminal investigation processes and to identify areas for improvement that may strengthen forensic services and inter-agency collaboration. Specifically, the study assessed the impact of PFT assistance in crime scene investigation, forensic analysis, training and capacity building, research and development, and coordination with other law enforcement agencies. The study employed a descriptive research design using simple random sampling. Respondents consisted of police officers assigned to the Tagaytay Component City Police Station (CCPS) and personnel from the Scene of the Crime Operatives (SOCO) unit located in Barangay Mendez Crossing East, Tagaytay City. Data were collected using a structured survey questionnaire and analyzed through statistical tools such as frequency distribution and weighted mean. Findings revealed that respondents generally rated the Provincial Forensic Team’s contribution as highly positive, particularly in improving crime scene investigation procedures, strengthening forensic analysis, supporting training initiatives, and enhancing collaboration among investigative agencies. However, several operational challenges were identified, including insufficient financial resources, outdated forensic equipment, heavy case workloads, and coordination inefficiencies, which may limit the effectiveness of forensic services. Based on these findings, the study recommends increased funding for forensic operations, modernization of forensic equipment and technology, continuous professional training for forensic personnel, and stronger collaboration among law enforcement and judicial agencies.